Prejudice between triage nurses and emergency medical technicians: is it a big deal? - Maiandi, Stefano; Galazzi, Alessandro; Villa, Alessandro; Zarini, Mariangela; Sironi, Stefano; Lusignani, Maura (Acta Biomedica Atenei Parmensis, 2021)
The transmission of information between registered nurses (RNs) and emergency medical technicians (EMTs) in triage plays a fundamental role in patient care. Despite their common purpose is to assure patients to get the best diagnostic, therapeutic and care pathway, triage RNs and EMTs hold different perspectives during the process. One aspect that has not been investigated in the international literature concerns the possible presence of prejudice, meant as a preconceived opinion capable of causing people to adopt unjust attitudes toward EMTs by triage RNs. To investigate this phenomenon a survey was conducted among 740 healthcare workers (197 triage RNs and 543 EMTs), in 14 hub and spoke hospitals in Lombardia region (Italy) in October 2019. The 21.9% of RNs reported negative prejudice toward EMTs (particularly if they are volunteer), while 71% of EMTs perceived negative prejudice from triage RNs. This survey did not investigate the phenomenon exhaustively but witnessed a slippery scenario that is worth to be further explored, also evaluating whether it can affect outcomes in patients.